Cultural Tourism: An Ethnographic Study of Home stay in Briddim Village, Nepal - Dong, Tek Bahdur (The Gaze: Journal of Tourism and Hospitality, 2020)
The present scenarios of global tourism reflect that growing not only in the number of tourists around the world but also significantly diffusion of global and tourists’ culture. While tourism brings different peoples together, question may beasked what happened when different societies, one as a host and the other as tourists, encounter in the social field. This study examines the local perspective of home stay tourism with the objective of how private houses and individuals are connected to global tourism and how host community and tourists influence each other lead for cultural change. By applying an ethnographic research methods and tools in the field and reviewing relevant literatures, I argue that home stay businesses not always associated with an economic aspect of profit and loss. Rather it has to be analyzed in the local situational context. Although home stay brought number of positive impacts especially directly employment, women empowerment, increased tourism skills, and community development, this will be incomplete analysis if we look only from the perspective of sustainable business. Engaging with anthropological theories on globalization and theory of cultural change, my study also highlights on cultural exchange between host community and tourists through which both local people and visitors feel change in some movement of their life. While few cultural changes were found among the tourists like food culture, i.e Dal-bhat and Masala tea, the host community was largely influenced by the tourists’ culture. The trekking guides are the best example of tourist culture as they wear tourists’ gears and acculturated with tourists’ norms and values. This culture now became a reality in part of their life with the interconnection of village and global tourism.